2016
DOI: 10.1007/s00464-016-5247-5
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics in the operating room

Abstract: BackgroundSince the introduction of minimally invasive surgery, surgeons appear to be experiencing more occupational musculoskeletal injuries. The aim of this study is to investigate the current frequency and effects of occupational musculoskeletal injuries on work absence.MethodsAn online questionnaire was conducted among all surgeons affiliated to the Dutch Society for Endoscopic Surgery, Gastrointestinal Surgery, and Surgical Oncology. In addition, this survey was conducted among surgeons, gynaecologists, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 42 publications
2
56
0
5
Order By: Relevance
“…68 Surgeons who suffer from a work-related injury may require an increased amount of sick leave, variations or limitations to their practice, temporary assignments to nonsurgical tasks, or early retirement. 4,19,69 Self-medication or analgesic usage may alleviate symptoms, but these treatment options do not target the underlying cause. The ultimate goal would be to recognize causative factors at early stages and employ countermeasures to minimize pain and disability while promoting career longevity.…”
Section: Musculoskeletal Therapymentioning
confidence: 99%
“…68 Surgeons who suffer from a work-related injury may require an increased amount of sick leave, variations or limitations to their practice, temporary assignments to nonsurgical tasks, or early retirement. 4,19,69 Self-medication or analgesic usage may alleviate symptoms, but these treatment options do not target the underlying cause. The ultimate goal would be to recognize causative factors at early stages and employ countermeasures to minimize pain and disability while promoting career longevity.…”
Section: Musculoskeletal Therapymentioning
confidence: 99%
“…The use of surgical ports creates a pivot point for the instruments in the body wall, which reduces the degrees of freedom (DoF) of the surgical instruments, from six (free motion) in conventional surgery to four in laparoscopic surgery, as illustrated in Figure 1. Besides, laparoscopic instruments suffer from ergonomically inadequate handle designs and inefficient transmission of force and tactile feedback from the handle to the instrument tip [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of display positioning in MIS, these axes are often misaligned, resulting in an ergonomic disadvantage. Multiple studies have demonstrated that this is an unfortunate downside to MIS and may result in excessive surgeon fatigue, discomfort, and work‐related musculoskeletal injuries . That being said, it is not surprising that the majority of surgeon discomfort appears to center around the neck and shoulders .…”
Section: Introductionmentioning
confidence: 99%